STUDI LITERATUR TENTANG MANAJEMEN PEMASARAN DIGITAL BAGI PROFESIONAL MAKEUP ARTIST DI ERA MEDIA SOSIAL - Ummah, Adisty Akhoma; Giatman, M.; Ernawati, Ernawati (Ensiklopedia of Journal, 2024)
Abstract: With the rapid development of social media, makeup artists face the challenge of constantly adapting to changing digital trends that affect how they build relationships with their audiences and market their services effectively. This study discusses effective digital marketing management strategies for makeup artists (MUAs) in the era of social media, focusing on platforms such as Instagram, TikTok, and YouTube. This literature study found that personal branding, educational content, collaboration with influencers, and data analysis are essential for attracting and retaining audiences and increasing loyalty. The main challenges include fierce competition, algorithm changes, and consistently producing quality content. These findings highlight the importance of developing digital marketing skills for MUAs to strengthen their competitiveness and visibility in the beauty industry.Keywords: Social Media, Digital Marketing, Makeup Artist, Personal Branding, Challenges.